None left to tell eaudiobook - Ihli, Noelle (Simon Maverick, 2025)
A riveting novel of historical suspense, from the bestselling author of Ask for Andrea , and based on the harrowing true story of the Mountain Meadows Massacre. Three women, connected by one of the most brutal mass slayings in US history. Lucy is sick of turning the other cheek. Ten years ago, an anti-Mormon mob drove her family and friends from their homes in Illinois. But now, the tables have turned. Rumor has it, some of those same men are traveling through Utah on their way to California. And this time, Lucy won't run. Katrina knew the trek west would be difficult. But she had no idea she'd be walking straight into hell. The young mother of four is prepared to do whatever it takes to protect her family from the violence closing in, but the battle to survive will be more harrowing than anything she can imagine. Sally has just been "gifted" to a man she barely knows—as his fourth wife. Trapped and lonely, she tries to make the best of her new life. But when her husband insists on joining a group of religious zealots' plans for revenge, she's forced to reconsider her loyalties. Even if it means putting her own life on the line. Based on true events, None Left to Tell is the story of the Mountain Meadows Massacre.